2014
DOI: 10.4172/2157-7595.1000174
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of an Internet-Based, African Dance-Modified Yoga Program for African-American Women with or at Risk for Metabolic Syndrome

Abstract: African-American (AA) women are the segment of the population that experiences the highest mortality from metabolic syndrome (MetS). Yoga decreases risk of MetS, yet there have been no yoga studies of AA women with or at risk for MetS. The purpose of this 4-week study was to test the feasibility and acceptability of a culturally tailored, Internet-based intervention, yogic dance (YD), using digital videos in a sample of AA women (ages 35-64) at risk for or with MetS. The investigators examined the rates of acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The Internet also provides researchers a better platform to conduct their studies. K Firestone (2014), Johnson (2014) conducted online surveys to collect data [29,30], which has some similarities to our study.…”
Section: Introductionmentioning
confidence: 71%
“…The Internet also provides researchers a better platform to conduct their studies. K Firestone (2014), Johnson (2014) conducted online surveys to collect data [29,30], which has some similarities to our study.…”
Section: Introductionmentioning
confidence: 71%
“…DT- and yoga-based approaches currently require face-to-face interaction and skilled trainers need to be available to work with live groups of students. However, new technologies are being developed to deliver such interventions remotely, both synchronously and asynchronously [ 92 ]. Can young adults be cost-effectively treated with such interventions, given the limited budgets of many institutions of higher education and our health care system?…”
Section: Issues For Future Development Of Mind–body Approaches To mentioning
confidence: 99%
“…Several qualitative studies examining the relationship between PA and social support have yielded mixed results (Durant et al, 2014; Johnson, Taylor, Anderson, Jones, & Whaley, 2014; Peterson & Cheng, 2011; Thomas et al, 2009). Thomas et al (2009), in focus groups with overweight or obese AAW, found that supportive behaviors believed to foster increased PA included having someone to exercise with, avoiding negative support such as criticism, and increased positive support such as praise from family member or friends.…”
Section: Interpersonal (Social) Support For Pamentioning
confidence: 99%